2017
DOI: 10.1021/acs.jafc.7b04612
|View full text |Cite
|
Sign up to set email alerts
|

Bioaccumulation of CeO2 Nanoparticles by Earthworms in Biochar-Amended Soil: A Synchrotron Microspectroscopy Study

Abstract: The interactions of nanoparticles (NPs) with biochar and soil components may substantially influence NP availability and toxicity to biota. In the present study, earthworms ( Eisenia fetida) were exposed for 28 days to a residential or agricultural soil amended with 0-2000 mg of CeO NP/kg and with biochar (produced by the pyrolysis of pecan shells at 350 and 600 °C) at various application rates [0-5% (w/w)]. After 28 days, earthworms were depurated and analyzed for Ce content, moisture content, and lipid perox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…It seems that the large reduction of Ce occurred in the snail DG only after ingestion, for Ce(IV) species predominate in the plant tissues and feces. The reduction of CeO 2 NPs has been observed in several species, such as Escherichia coli, 43 plants, 12 nematodes, 44 earthworms, 45 and freshwater snails. 34 Moreover, we have demonstrated that natural reducing substances and organic acids in root exudates play important roles in the reduction of CeO 2 NPs in plants.…”
Section: Environmental Science and Technologymentioning
confidence: 99%
“…It seems that the large reduction of Ce occurred in the snail DG only after ingestion, for Ce(IV) species predominate in the plant tissues and feces. The reduction of CeO 2 NPs has been observed in several species, such as Escherichia coli, 43 plants, 12 nematodes, 44 earthworms, 45 and freshwater snails. 34 Moreover, we have demonstrated that natural reducing substances and organic acids in root exudates play important roles in the reduction of CeO 2 NPs in plants.…”
Section: Environmental Science and Technologymentioning
confidence: 99%
“…The former, however, can create two-dimensional images that are accurate representations of the latter technique and can generate three-dimensional pictures by measuring the elemental distribution of the monitored analyte. The spatial resolution of a synchrotron-generated XRF beam is normally between 1 and 10 m, but some XRF beams have a spatial resolution of up to 100 m. Beamlines for sub-micrometer analysis are available and provide a spatial resolution of up to 100 nm [ 33 ].…”
Section: Bioanalytical Methods For the Determination Of Nanoparticlesmentioning
confidence: 99%
“…Interestingly, most studies have been done with earthworms (74.1%), isopods (16.28%), and collembola (9.30%), and the majority carried out under laboratory conditions, but the main reason for the use of these organisms is because they are the classes of invertebrates with the highest representation in biomass and the with ability to decompose and transform OM (Kautz and Topp 2000). They appear to be suitable as bioindicator organisms for ecotoxicity studies on new xenobiotics such as nanoparticles (Flaccavento et al 2019;Servin et al 2018). For this experiment, even when demonstrated adverse effects under greenhouse conditions, these data let us suggest that in agricultural or forestry area, TiO 2 NPs may impact organisms' populations.…”
Section: Number Weight and Concentration Of Ti In Isopods And Ti Concentration In Organic Matter And Soilmentioning
confidence: 99%